Wegbegleitung, Trost und Hoffnung Interdisziplinäre Beiträge zum Umgang mit Sterben, Tod und Trauer - Jungbauer, Johannes; Krockauer, Rainer (Schriften der KatHo NRW, 2013)
What may be done when a person is dying? Accompany and thus give comfort - but how? The contributions of this interdisciplinary volume give professional or individual advice to people confronted with death on how to support dying people in their last days and hours. In this way they lead to a holistic palliative and terminal care.